2011
DOI: 10.1002/ajh.21952
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructing sickle cell disease: A data‐based analysis of the “hyperhemolysis paradigm” for pulmonary hypertension from the perspective of evidence‐based medicine

Abstract: The ''hyperhemolytic paradigm'' (HHP) posits that hemolysis in sickle disease sequentially and causally establishes increased cell-free plasma Hb, consumption of NO, a state of NO biodeficiency, endothelial dysfunction, and a high prevalence of pulmonary hypertension. The basic science underpinning this concept has added an important facet to the complexity of vascular pathobiology in sickle disease, and clinical research has identified worrisome clinical issues. However, this critique identifies and explains … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
158
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(166 citation statements)
references
References 292 publications
(523 reference statements)
6
158
1
1
Order By: Relevance
“…The sickle myocardium has been presumed to be relatively resistant to the effects of sickling (10), and studies/autopsies show little evidence of atherosclerosis or coronary disease (11)(12)(13)(14). Mildly increased systolic pulmonary arterial pressure (PAP) estimated by tricuspid regurgitant jet velocity (TRV) of >2.5 m/s by echocardiography has been shown to be an independent risk factor for early mortality (odds ratio 8-15) (5,(15)(16)(17)(18)(19)(20). This finding was initially considered to be consistent with pulmonary arterial hypertension (PH) (5,17,(21)(22)(23)(24)(25).…”
mentioning
confidence: 53%
“…The sickle myocardium has been presumed to be relatively resistant to the effects of sickling (10), and studies/autopsies show little evidence of atherosclerosis or coronary disease (11)(12)(13)(14). Mildly increased systolic pulmonary arterial pressure (PAP) estimated by tricuspid regurgitant jet velocity (TRV) of >2.5 m/s by echocardiography has been shown to be an independent risk factor for early mortality (odds ratio 8-15) (5,(15)(16)(17)(18)(19)(20). This finding was initially considered to be consistent with pulmonary arterial hypertension (PH) (5,17,(21)(22)(23)(24)(25).…”
mentioning
confidence: 53%
“…It was therefore concluded that pulmonary hypertension in sickle cell patients is caused by a complex, multifactorial pathophysiology that may involve NO depletion, vasoconstriction, thromboembolic vascular occlusion, left ventricular impairment, chronic vascular remodeling, and secondary hemodynamic effects caused by the hyperdynamic circulation that occurs in many patients with more severe or chronic anemia. 64,65 The quantitative contributions of these individual factors and the specific role of free Hb and hemin in the pathophysiology of vascular complication in sickle cell disease remain an important area for further mechanistic evaluation in clinical settings.…”
Section: The Role Of Hb Heme and Their Scavenger Proteins In Specifmentioning
confidence: 99%
“…The widely variable severity of symptoms and target organ damage even within similar phenotypes depends on the extent of vascular inflammation/injury, cellular/ chemokine changes, and the induction of a hypercoagulable state that is blamed on inflammatory pathways spurred by nitric oxide depletion, C-reactive protein, inflammatory cytokines such as IL-6, and adhesion molecules. 1,2 However, the level of contribution of individual pathways is unclear, making targeted pharmacologic intervention complicated. 3 Although not curative, there have been significant advances in supportive care for SCD in the last decade.…”
Section: Introductionmentioning
confidence: 99%